Avaliação de um sistema eólio-elétrico de bombeamento de água - Lopes, Luiz Carlos Nascimento (2011)
This dissertation implements the plant of an unit of pumping water supplied by electricity from the wind energy, to make possible the wells water extraction in semi-arid regions installed at the Station of Engineering Fishing on Pici's Campus of University Federal of the Ceará (UFC), in Fortaleza - CE, Brazil. The unit has a wind turbine (1kW-220 Vac), a load controller, and a water pumping system from a well to an elevated reservoir. The electricity to water pumping system can be powered by wind turbine or conventional grid. Other aspect that improves the work was the development of a piping that can be configured to submit the water pumping system to several hydraulics loads to accomplish the operational tests. The developed plant was able to pump, on an average, 4.318 L/day of water with the maximum value of 10.698 L/day to an average wind speed of 3,84 m/s. The reached average efficiency were : 10% (wind/hydraulic) and 41% (electric/hydraulic) by a wind speed of 6,5 m/s. The accomplished rehearsals demonstrated low robustness of the wind turbine used, pledging, thus, the operational availability and the equipment reliability. Actions are suggested to guarantee the viability of this model of water pumping powered by small size wind turbines.